Space charge effects and RF focusing of ribbon beam in ion linac - Masunov, E.S.; Vinogradov, N.E.; Polozov, S.M. (Вопросы атомной науки и техники, 2001)
Version of the plane structure ion linac which is designed for intensive low energy ribbon beams bunching and acceleration is considered. Transverse stability is achieved by the use of nonsynchronous field harmonic focusing influence (RF focusing concept). Investigation of intensive ribbon beam dynamics features is carried out. The space charge effects are studied numerically by means of "super particles" approach. The proposal of 80% transmission 1 A limit current ribbon beam accelerator for the ITER neutral injection system and some another applications is presented.